Furio Jesi teorico della traduzione - Dogà, Ulisse (Edizioni Ca’ Foscari, 2021)
The figure of the cultural anthropologist Furio Jesi has experienced a major rediscovery in recent years thanks to the commendable republication of his books and the publication of numerous unpublished works. In this rediscovery, however, a non-secondary aspect of this multifaceted author still remains in shadow, namely his philosophical and hermeneutic interest in the idea of translation. There are many traces of Jesi’s interest in the theory of translation. A volume entitled Translation and Duplicity of Languages was not completed, but there are some chapters from this project (already published in magazines) and materials still awaiting publication. After the study of Walter Benjamin’s Essays on Language, translation represents for Jesi a fundamental ‘linguistic’ junction of the relationship between the sacred and the profane, between myth and mythologem, between the origin and history of language. The aim of this essay will be to reconstruct and clarify Jesi’s idea of ‘translatability’, trying to trace a common thread among the theoretical essays in which Jesi determines translation as a further gnoseological background of his ‘mythological machine’ on the one hand, and the excursus of history of the language and his critical essays on literature on the other.